Nilai-Nilai Keagamaan Katolik Dalam Pembentukan Moral Anak Di Paroki Santo Yosef Delitua - Kurniadi, Benediktus Benteng; Fajariyanto, Tri Chandra; Br Ginting, Yova Andriani (Titian: Jurnal Ilmu Humaniora, 2022)
Abstract: This study aims to describe the implementation of children's moral education by parents in Paroki Santo Yosef Delitua. The research applies descriptive qualitative method by using interview, observation and documentation by 7 (seven) rayons/areas of the Paroki Santo Yosef Delitua. The description of the implementation of moral education for children by parents at the Paroki Santo Yosef Delitua is related from several aspects. This aspect shows the implementation of children's moral education by parents. The first aspect is related to parents having an understanding and knowledge of the importance of children's moral education. Parents are the first and foremost educators of children. Thus, parents become moral role models for children. The second aspect is related to parental support to be realized in words. Furthermore, the third aspect, namely the implementation of children's moral education by parents, is reflected in daily life, namely the freedom of will, responsibility, and the linkage of moral and Christian moral norms which are manifested in everyday life. Keywords: children; children’s moral education